Risk model validation : a practical guide to addressing the key questions - Meyer, Christian; Quell, Peter (London : Risk Books, 2011)
The report aims to explain: What risk model validation is; What risk models exist; How a risk model can fail; Which aspects of reality are included, and which aspects are excluded from a risk model; and How business decisions can be based on a risk models' output.
Includes bibliographical references and index.
oif 15/10/15
Loan
Keywords: Risk management; Risk management -- Mathematical models